Edukasi Kesehatan dalam Pengambilan Keputusan dan Perilaku Mencari Pengobatan pada Pasien Akut Miokard Infark - Ningrum, Beti; Herawati, Tuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify health education in treatment decision-making and treatment-seeking behavior in AMI patients. The research method used was a systematic review with a literature search strategy using six databases: Pubmed, Science Direct, Scopus, Proquest, Taylor & Francis Online, and Clinical Key Nursing. The research results show that health education for AMI patients to improve decision-making and treatment-seeking behavior consists of narrative-based health education and decision-making aid. In conclusion, health education for patients or families can improve patients and families' decision-making and increase behavior in seeking health assistance in patients or families in AMI patients. Keywords: Acute Myocardial Infarction, Health Education, Treatment Seeking Behavior